PURBA 2015: The 4th workshop on pervasive urban applications - Santi Phithakkitnukoon (2018)
© Copyright 2015 ACM. This is the proposal for the Forth Workshop on Pervasive Urban Applications (PURBA 2015). The workshop aims to build on the success of the previous workshops organized in conjunction with the Pervasive 2011, Pervasive 2012, and UbiComp 2013, to continue to disseminate the results of the latest research outcomes and developments of ubiquitous computing technologies in urban areas. All workshop contributions will be published in supplemental proceedings of the UbiComp 2015 conference and included in the ACM Digital Library.